Prenatal Exposure to Per- and Polyfluoroalkyl Substances and Childhood Autism-related Outcomes. Issue 3 (3rd April 2023) - Ames, Jennifer L.; Burjak, Mohamad; Avalos, Lyndsay A.; Braun, Joseph M.; Bulka, Catherine M.; Croen, Lisa A.; Dunlop, Anne L.; Ferrara, Assiamira; Fry, Rebecca C.; Hedderson, Monique M.; Karagas, Margaret R.; Liang, Donghai; et al.
Abstract : Background: Epidemiologic evidence linking prenatal exposure to per- and polyfluoroalkyl substances (PFAS) with altered neurodevelopment is inconclusive, and few large studies have focused on autism-related outcomes. We investigated whether blood concentrations of PFAS in pregnancy are associated with child autism-related outcomes. Methods: We included 10 cohorts from the National Institutes of Health (NIH)-funded Environmental influences on Child Health Outcomes (ECHO) program (n = 1, 429). We measured 14 PFAS analytes in maternal blood collected during pregnancy; eight analytes met detection criteria for analysis. We assessed quantitative autism-related traits in children via parent report on the Social Responsiveness Scale (SRS). In multivariable linear models, we examined relationships of each PFAS (natural log-transformed) with SRS scores. We further modeled PFAS as a complex mixture using Bayesian methods and examined modification of these relationships by child sex. Results: Most PFAS in maternal blood were not associated with child SRS T-scores. Perfluorononanoic acid (PFNA) showed the strongest and most consistent association: each 1-unit increase in ln-transformed PFNA was associated with greater autism-related traits (adjusted β [95% confidence interval (CI)] = 1.5 [–0.1, 3.0]). The summed mixture, which included six PFAS detected in >70% of participants, was not associated with SRS T-scores (adjusted β [95% highest posterior density interval] = 0.7 [–1.4, 3.0]). We did not observe consistent evidence of sex differences. Conclusions: Prenatal blood concentrations of PFNA may be associated with modest increases in child autism-related traits. Future work should continue to examine the relationship between exposures to both legacy and emerging PFAS and additional dimensional, quantitative measures of childhood autism-related outcomes.